Haematological, neurological and electrocardiographic findings in secondary hypothermia. (16th November 2012) - Dickinson, Oana; Hanson, Brian; Benditt, David G; Duran-Nelson, Alisa M
Abstract : The association between secondary hypothermia and pancytopaenia is uncommon. A young woman presented with chronic hypothermia (28.8–34.6°C) secondary to surgical hypothalamic injury postcraniopharyingioma resection as a child. Associated findings included pancytopaenia (haemoglobin 8.1 g/dl, leucocytes 3500/mm 3, platelets 63 000/mm 3 ), ataxia, upper motor neuron signs, decreased level of consciousness and new ECG changes. An extensive evaluation failed to reveal any cause of pancytopaenia other than chronic hypothermia. The haematological and neurological changes improved after active rewarming.